Analisis Pengaruh Kepemimpinan, Motivasi dan Disiplin Kerja Terhadap Kinerja Karyawan Toko Raysa Pemadam Joglo - Ade Setiawan (CV. Syntax Corporation Indonesia, 2022)
The obstacle that often occurs is when the delivery schedule is delayed, in this situation good work discipline is needed, so that it can be followed up as soon as possible so as not to cause disappointment from consumers. This study aims to describe the problems that exist in the Raysa Pemadam Store where the development of the basic household needs business sector (sembako) is an opportunity for small companies for sub-sectoral work. Take advantage of opportunities to reach consumers, create competition between similar repair service companies. This also makes every company must innovate creative marketing strategies in selling the goods offered to the target audience. This study aims to determine the effect of leadership, motivation and work discipline on employee performance, for leadership partially employee performance. The type of research used in this paper is descriptive research, using a qualitative approach. The results obtained are that Raysa Pemadam Joglo Shop is a small business in the field of household needs (Sembako) in Joglo, West Jakarta. The results obtained are that these small and medium enterprises (MSMEs) carry out good leadership with employees, motivate employees in the form of rewards to their employees and also have a good level of discipline where there are very few complaints from consumers